1984
DOI: 10.1111/j.1365-2621.1984.tb13725.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Small Sample Back Extrusion Test for Measuring Texture of Cooked Sorghum Grain

Abstract: A small sample back extrusion test cell mounted in an lnstron Universal testing machine was used to measure the texture of cooked whole and decorticated sorghum grains. Measurements were done on 8-g (undecorticated grain) and 10-g (decorticated grain) cooked samples of 11 sorghum cultivars. The cultivars differed widely in percent vitreousness. The percent vitreousness data significantly correlated to the back extrusion energy values of cooked whole grain (r= 0.91**) and cooked decorticated grain (r=0.94**). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Crosshead speed was 100 mm/min, and the peak force was registered in Newtons as a measure of the batter resistance to flow. A similar method was described by Seman et al (1980) for meat emulsions, by Cagampang et al (1984) for cooked sorghum grain, and by Reyes and Jindal (1990) for cooked rice.…”
Section: Batter Back-extrusion Testmentioning
confidence: 97%
“…Crosshead speed was 100 mm/min, and the peak force was registered in Newtons as a measure of the batter resistance to flow. A similar method was described by Seman et al (1980) for meat emulsions, by Cagampang et al (1984) for cooked sorghum grain, and by Reyes and Jindal (1990) for cooked rice.…”
Section: Batter Back-extrusion Testmentioning
confidence: 97%
“…Anzaldua- Morales and Brennan (1982) correlated the back extrusion force of canned baked beans with the maximum compression force of dry beans. Cagampang, Kirleis, and Marks (1984) applied the back extrusion technique for measuring the texture of boiled sorghum seed. Gandi and Bourne (1991) used the back extrusion technique to study the effects of soaking and cooking time on thermal softening of soybeans.…”
Section: Introductionmentioning
confidence: 99%
“…Cooked weight was higher for samples from the small size class, indicating greater water absorption. Cagampang, Kirleis, and Marks (1984) reported that soft sorghum grain absorbed more water during cooking that hard grain. Although we did not directly test the effect of hardness on water absorption, our results support that conclusion since small kernels were shown to be softer than large kernels in all seedlots (Table 2).…”
Section: Cooking Quality Of Decorticated Grainmentioning
confidence: 99%